CONSTRAINTS FACED BY THE ORGANIC FARMERS IN THE EASTERN PLAIN OF RAJASTHAN (International Journal of Food and Nutritional Sciences, 2023)
Despite having 30% of the world's organic producers, India only has 2.59% of the world's total organic agriculture land. The farmers of eastern plain of Rajasthan are still facing various types of constraints in adoption of organic farming; hence the study entitled “Constraints Faced by the Organic farmers in the Eastern Plain of Rajasthan” was conducted in eleven villages covering 576 respondents comprising of certified organic farmers. With the help of a pre- tested interview schedule, a survey was conducted to collect relevant data and then appropriate statistical procedure was employed to analyze the data for assessing the effect of different constraints in the adoption component. Findings revealed that majority of the certified organic farmers faced constraints i.e. 65.67 percent were agreed that they had lack of up to-date knowledge about organic agricultural technology, 78.68 per cent had initial low price for the organic produce as severest issue, 74.69 percent were facing the problem of lack of specialized markets for organic produce etc.